A (2, 2) Visual Cryptography Technique with Improved Contrast. Issue 4 (3rd July 2020) - Bhosale, Akshay Gajanan; Patil, Vikram Shripati
ABSTRACT: Visual cryptography is a technique used to share a secret among many participants. The problem with visual cryptography technique is that the secret is not perfectly recovered, i.e. a black secret pixel is perfectly recovered but a white secret pixel is recovered with less contrast. Because of this, the overall quality of recovered secret is poor. So to improve the quality of recovered secret image, we need to improve the contrast. In this paper, we have proposed a (2, 2) visual cryptography technique with improved contrast as compared to the traditional (2, 2) visual cryptography scheme (VCS). In the proposed technique, we have used additional basis matrices for encrypting the secret pixels. The quality of the recovered secret image is compared with traditional (2, 2) VCS using various image quality metrics.